Stable Electrochromic Polyschiff Bases Containing Triarylamine Units: Synthesis, Electrochemical, and Acidochromic Properties. Issue 5 (24th March 2018) - Xiao, Tian-di; Ji, Yan; Cai, Wan-an; Zhang, Xu; Niu, Hai-jun; Wang, Cheng; Jiang, Xian-kai; Wang, Wen
ABSTRACT: Four polySchiff bases containing different triphenylamine moieties were synthesized based on the polycondensation reaction of 4-methyl-4′, 4″-diformyltriphenylamine with various aromatic diamines which contain triphenylamine groups. Especially, 4-methyl-4′, 4″-diformyltriphenylamine was obtained by the reduction of compound with nitril groups with diisiobutylaluminum hydride. The structures of 4-methyl-4′, 4″-diformyltriphenylamine and polySchiff bases were confirmed by Fourier transform infrared and the nuclear magnetic resonance techniques. The polySchiff bases displayed good thermal stability, with 5% weight loss above 450°C under nitrogen atmosphere. All the polymer films exhibited good electrochemical and electrochromic stability under repeatedly switching electrode voltages. Take the polySchiff base-d, for example, the color changed from the pale yellow neutral state to green and crimson oxidized state at applied potentials ranging from 0.0 to 1.6 V. The polySchiff bases showed obvious acidochromic properties. The polySchiff bases exhibited a typical photovoltaic response and good stability. Consequently, the polySchiff bases would be promising electrochromic and acidochromic materials. GRAPHICAL ABSTRACT: